The Effect of Nanoparticles Turmeric Consumption (Curcuma Domestica Val) on Blood Pressure and Lipid Profile in Hypertension Patients with Hypercholesterolemia - Mardiyono; Daryanti Daryanti; Rr. Sri Endang Pujiastuti (International Journal of Nursing and Health Services (IJNHS), 2021)
Introduction: The main risk factors for blood pressure disease are hypertension, smoking, and elevated cholesterol. Irregularities in lifestyle and lifestyle cause health problems that can cause death, such as hypertension. Objective: The study aimed to examine the effectiveness of the giving nanoparticles turmeric consumption on blood pressure and lipid profile in hypertension patients with hypercholesterolemia. Methods: This study applied the true experiment, pretest-posttest design with a non-equivalent control group design. Data collection involved 42 respondents with a medical diagnosis of hypertension with hypercholesterolemia, selected through a probability sampling technique with a method of simple random sampling, divided into two groups of 21 respondents each. Data analysis using Paired t-test and independent t-test. Results: Independent t-test showed a significant difference p value <0.05 that the intervention group is better in reducing systolic and diastolic blood pressure, total cholesterol, HDL, LDL, and triglycerides compared with the control group. Conclusion: Consumption of turmeric nanoparticles (Curcuma Domestica Val) is effective in lowering blood pressure and lipid profile (total cholesterol, HDL, LDL, and triglycerides) in hypertension patients with hypercholesterolemia